Investigation antibacterial application and mechanism of the cyclodextrin-metal-organic framework loaded with gold nanoparticle - Meimei Guo; Tahirou Sogore; Tian Ding; Mofei Shen (CyTA - Journal of Food)
The severe threat of microbial contamination to human life and health safety necessitates urgent research and development of antimicrobial materials capable of inhibiting or eradicating pathogens. Cyclodextrin metal-organic framework (CD-MOF) was utilized as a carrier to encapsulate gold nanoparticles (AuNPs), resulting in a composite material (Au@CD-MOF) that exhibited remarkable antibacterial properties. The antibacterial study revealed that Au@CD-MOF completely eradicated Staphylococcus aureus (S. aureus) and Listeria monocytogenes (L. monocytogenes) at a concentration of approximately 1 × 105 CFU/mL after 48 h and 36 h, respectively. Moreover, Au@CD-MOF also demonstrated the complete elimination of Escherichia coli O157:H7 (E. coli O157:H7), Pseudomonas aeruginosa PAO1 (P. aeruginosa PAO1), and Salmonella typhimurium (S. typhimurium) at a concentration of approximately 1 × 105 CFU/mL after 48 h. Moreover, the antibacterial mechanism of Au@CD-MOF was investigated using E. coli O157:H7 and S. aureus as model organisms. The findings revealed that Au@CD-MOF disrupted the integrity of cell membranes and diminished their potential, consequently impeding the normal functions of the bacteria. Additionally, the heightened permeability of cell membranes induced by Au@CD-MOF resulted in substantial leakage of nucleic acids and proteins, ultimately leading to bacterial eradication.